Vapour pressure measurements of liquid heavy water in the temperature range between 256 K and 286 K. (October 2021) - Beltramino, G.; Rosso, L.; Cuccaro, R.; Fernicola, V.
Highlights: New accurate saturation vapor pressure measurements of liquid heavy water. Investigated temperature range includes an interval of 21 K in the supercooled region. Measurement traceability to the SI units. Accurate evaluation of the measurement uncertainty is provided. Comparison of the experimental data with the most recent D2 O formulations. Abstract: The thermodynamic properties of heavy water (D2 O) are important in industrial applications as well as in the scientific domain, where the understanding of the isotopic effects in aqueous solutions is relevant. In contrast with ordinary water (H2 O), comparatively few saturation vapour pressure measurement data of D2 O are reported in the literature in the temperature range where heavy water is in its supercooled state and often are provided with a poor or even unknown measurement uncertainty estimate. In this work accurate measurements of the vapour – liquid equilibrium along the saturation line of heavy water over the temperature range from 256 K to 286 K are performed, encompassing a relatively wide temperature range where heavy water is in its supercooled state (256 K–277 K). A comparison between the experimental measurements performed in this work and the available literature data is also carried out along with the recent D2 O vapour pressure formulation. Measurement results are discussed and uncertainty sources are estimated.